Cost-Effectiveness of Initiating Pharmacological Treatment in Stage One Hypertension Based on 10-Year Cardiovascular Disease Risk: A Markov Modeling Study. Issue 2 (February 2021) - Constanti, Margaret; Floyd, Christopher N.; Glover, Mark; Boffa, Rebecca; Wierzbicki, Anthony S.; McManus, Richard J.
Abstract : Antihypertensive drug treatment is cost-effective for adults at high risk of developing cardiovascular disease (CVD). However, the cost-effectiveness in people with stage 1 hypertension (140–159 mm Hg systolic blood pressure) at lower CVD risk remains unclear. The objective was to establish the 10-year CVD risk threshold where initiating antihypertensive drug treatment for primary prevention in adults, with stage 1 hypertension, becomes cost-effective. A lifetime horizon Markov model compared antihypertensive drug versus no treatment, using a UK National Health Service perspective. Analyses were conducted for groups ranging between 5% and 20% 10-year CVD risk. Health states included no CVD event, CVD and non-CVD death, and 6 nonfatal CVD morbidities. Interventions were compared using cost-per-quality-adjusted life-years. The base-case age was 60, with analyses repeated between ages 40 and 75. The model was run separately for men and women, and threshold CVD risk assessed against the minimum plausible risk for each group. Treatment was cost-effective at 10% CVD risk for both sexes (incremental cost-effectiveness ratio £10 017/quality-adjusted life-year [$14 542] men, £8635/QALY [$12 536] women) in the base-case. The result was robust in probabilistic and deterministic sensitivity analyses but was sensitive to treatment effects. Treatment was cost-effective for men regardless of age and women aged >60. Initiating treatment in stage 1 hypertension for people aged 60 is cost-effective regardless of 10-year CVD risk. For other age groups, it is also cost-effective to treat regardless of risk, except in younger women. Abstract : Supplemental Digital Content is available in the text.